Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1073/pnas.1804740115
|View full text |Cite
|
Sign up to set email alerts
|

GEF mechanism revealed by the structure of SmgGDS-558 and farnesylated RhoA complex and its implication for a chaperone mechanism

Abstract: SmgGDS has dual functions in cells and regulates small GTPases as both a guanine nucleotide exchange factor (GEF) for the Rho family and a molecular chaperone for small GTPases possessing a C-terminal polybasic region followed by four C-terminal residues called the CaaX motif, which is posttranslationally prenylated at its cysteine residue. Our recent structural work revealed that SmgGDS folds into tandem copies of armadillo-repeat motifs (ARMs) that are not present in other GEFs. However, the precise mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…2A). Crystallography studies recently confirmed these structural differences in ARM domains between the 2 isoforms (26,27).…”
Section: An Elevated 607:558 Splice Variant Ratio Is Expressed In Canmentioning
confidence: 79%
See 2 more Smart Citations
“…2A). Crystallography studies recently confirmed these structural differences in ARM domains between the 2 isoforms (26,27).…”
Section: An Elevated 607:558 Splice Variant Ratio Is Expressed In Canmentioning
confidence: 79%
“…This possibility is supported by our finding that lowering the 607:558 ratio by overexpressing SmgGDS-558 induces apoptosis. SmgGDS-558 can promote the cytosolic accumulation of prenylated small GTPases (46)(47)(48), which occurs by SmgGDS-558 shielding the prenyl group of the GTPase from the aqueous environment of the cytosol (27). Other chaperones of prenylated GTPases, including PDEδ (49,50), PRA1 (49,51), VPS35 (52), and RhoGDI (53), similarly solubilize prenylated GTPases by shielding the prenyl group of the GTPase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional binding experiments revealed that the selectivity of the Ric8A/Gα interaction is determined, in part, by a few class-specific residues of Gα, particularly those at positions corresponding to I340 and N343 of Gα t . Armadillo proteins that are structurally related to Ric8A, including SmgGDS β-catenin, and importin-α, commonly bind their partners at the concave surface 4143 . However, the nature of the ligand-binding interactions of Ric8A differs from those of other ARM-repeat proteins (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…RAP1GDS1 also binds other small GTPases including KRAS (37). RAP1GDS1 differs structurally from canonical RHO and RAS GEFs (38) and may also act as a chaperone for these small GTPases (39). The CDKO screens point to specific GIs among RAP1GDS1, RHOA and mutant KRAS not previously reported.…”
Section: Rap1gds1 and Rhoa Form A Synthetic Lethal Gene Pair In Ras-dmentioning
confidence: 77%